Socialitation and Simulation Game of the Volleyball Sand Sport in Babar Islands District of Southwest Maluku Regency - Mieke Souisa; Jacob Anaktototy; Jusak Syaranamual (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2021)
Since 1996 the volleyball sand sports have developed in Maluku province, and there has been vocation in PON as well as being one of the regular sport events of the province Maluku. But volleyball sand sport is known only to a view counties and cities in Maluku province. Such the cities of Southeast Maluku (Tual), the Regency of Tanimbar Island (Saumlaki), the Regency of Buru Island (Namlea), and Ambon City. But in Southwest Regency (Moa), the volleyball sand sports is now means to know until this day. Than Southwest Regency MOA has never include the sport branch in both the POPMAL administration and the state of the region. Event without it’s being recognized as a means of development for the regency of Southwest Maluku. Babar Islands is one of the sub district in Maluku Southwest, it is far from the capital of Southwest Regency (MOA) and Maluku Province. It is a analized factor in the development of the volleyball sand sport branch on Kalwedo Earth. Thus community service activities that embody the volleyball basic skills by college of the academy of arts and sciences, perform devotionals aimed at introducing a volleyball sand sport to the community and those responsible. The method uses for achieving goals in this community service is: 1) identification problem, 2) social approach, 3) planning, 4) administration management, 5) matrial preparation, 6) execution, 7) reporting. The results is: 1) participants of both the sons and doughters volleyball and the socialist-in volved volleyball. 2) participants understand the rules of volleyball sand game. 3) entry to the games own game. 4) the means and infrastructure of the game’s of the volleyball games. 5) the volleyball sand sport and infrastructure help during public service activities by lecture and collages of study programe physical education in Babar Islands